MANAJEMEN KOMUNIKASI KREATIF TIM PROGRAM “EPL” DI MNCTV - Wulandari, Yulianti Fajar; Bastian, Yan (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2019)
EPL or English Premier League is a professional football league in England, a prestigious competition, and has the highest ranking in broadcasting in the United Kingdom. The EPL program is a favorite program for soccer fans in Indonesia and broadcast on MNCTV. This study investigated how the communication management strategy of the EPL Creative Team in MNCTV in increasing ratings and shares as a measure of the success of a TV program. This study uses a constructivist paradigm with a qualitative-descriptive analysis of communication strategies and program production. From the lens of the organization control theory and management strategy, this study found that ideas were the key to the Creative Team in increasing the rating and share of the "EPL" program on MNCTV. The "EPL" creative communication management strategy in MNCTV can also apply to other MNCTV programs. To cite this article (7th APA style): Bastian, Y & Wulandari, Y. F. (2019). Manajemen Komunikasi Kreatif Tim Program “EPL” di MNCTV [Creative Communication Management of “EPL” Program Team in MNCTV]. Journal Communication Spectrum, 9(2), 158-175. http://dx.doi.org/10.36782/jcs.v9i2.1953